Organisation Of Academic Records In Public Secondary Schools In Education District One In Lagos State - Onikoyi Olawale Abayomi; Onikoyi Yetunde Raliat Adeola; Bankole Olabisi Latifat; Nafiu Aminat Adejoke (Jurnal Aktual Pendidikan Indonesia, 2026)
The purpose of this study was to ascertain how academic records are organised at public secondary schools located in Lagos State's Education District one. The attainment of efficient school organisation will always be at a crossroads if school heads do not rigorously follow the guidelines for accurate and efficient records keeping administration. In a similar vein, inadequate and erroneous documentation within the educational system hinders comprehension of actual school events and activities. As a result, this study is crucial to advancing corrective measures in the case that secondary schools in Lagos State to maintain erroneous and subpar data. The study was carried out with three research questions and three hypothesis. A questionnaire created by the researcher was utilized to gather information from 120 educators and 10 school heads who were chosen at random from the 10 public secondary schools in Education District one. The following two key conclusions were drawn from the respondents' responses. The handling of records in the secondary school system is fraught with issues. The school system's record-keeping will improve holistically through a variety of optimal organisational techniques and tactics. It was suggested that school heads and educators use the best organisational techniques and methods to enhance the secondary school system's records-keeping organisation in order to guarantee accurate and trustworthy school data in light of these findings.